The Influence of Environmental, Social, and Governance (ESG) Implementation and Sustainability Strategies on Corporate Financial Performance - Ainorrofiqie Ainorrofiqie; Fuji Santoso (Journal of Management and Creative Business, 2026)
The growing emphasis on sustainable business practices has motivated companies to incorporate Environmental, Social, and Governance (ESG) principles alongside sustainability strategies into their operations. Nevertheless, previous studies have produced mixed results regarding the impact of ESG on financial performance, while research examining the combined influence of ESG and sustainability strategy remains limited, particularly in Indonesia. This study investigates the effects of ESG implementation and sustainability strategy on corporate financial performance. Using a quantitative explanatory design, the research applies Partial Least Squares Structural Equation Modeling (PLS-SEM) to data from companies listed on the Indonesia Stock Exchange that consistently published annual and sustainability reports during the observation period. The findings reveal that both ESG implementation and sustainability strategy positively and significantly influence financial performance. The structural model further indicates that these variables jointly explain 69% of the variation in financial performance. The results suggest that integrating ESG practices with sustainability-oriented strategies enhances operational effectiveness, strengthens corporate reputation, and supports long-term value creation. This study enriches the literature by providing empirical evidence of the complementary roles of ESG and sustainability strategy in improving corporate financial outcomes.